Hangekobokuto (Banxia-houpo-tang), a Kampo Medicine that Treats Functional Dyspepsia. Issue 3 (2009) - Oikawa, Tetsuro; Ito, Go; Hoshino, Takayuki; Koyama, Hidehiko; Hanawa, Toshihiko
Abstract : Although abdominal bloating is one of the most bothersome symptoms experienced by patients with functional dyspepsia (FD), therapeutic drugs to relieve abdominal bloating have not been established. We investigated the Kampo (Chinese herbal) medicine, Hangekobokuto (Banxia-houpo-tang, HKT) for patients with FD from the standpoint of bowel gas retention. The bowel gas volume calculated from a plain abdominal radiogram (gas volume score, GVS) in FD patients was significantly higher than that in healthy subjects. Two week administration of HKT in the FD patients showed a significant decrease of GVS. Furthermore, gastrointestinal symptoms, especially symptoms of abdominal pain, indigestion and constipation, all of which are closely related to abdominal bloating, improved significantly in FD patients after the administration of HKT. These results suggest that HKT improves abdominal bloating accompanied by the reduction of bowel gas in FD patients.